Exploring the antioxidant effects of Aloe vera: Potential role in controlling liver function and lipid profile in high fat and fructose diet (HFFD) fed mice - Abdullahi Mukhtar Abubakar; Nathan Isaac Dibal; Martha Orendu Oche Attah; Samaila Musa Chiroma (Elsevier, 2022)
Background: Fat-rich diets are believed to induce obesity and contribute to the development of diabetes and cardiovascular disease in contrast high fructose diet was reported to increase gut surface area and enhance nutrient uptake resulting in weight gain. The study investigated the role of Aloe vera supplementation on oxidative stress, lipid profiles, and liver histology in high fat and fructose diet-fed mice. Methodology: Twenty mice were distributed into four groups (n = 5). The groups received a regular diet, high fat and fructose diet (HFFD), HFFD plus 10% Aloe vera (HFFD+AV1), and HFFD plus 20% Aloe vera (HFFD+AV2) respectively, for 10 weeks. Lipid profile and liver function were evaluated from the serum, antioxidant activities were evaluated from liver homogenate while the liver was processed for light microscopy. Results: The cholesterol level of HFFD+AV treated mice was significantly lower compared to HFFD treated mice. The alanine aminotransferase (ALT) level was significantly increased in HFFD-treated mice relative to the control. Aloe vera significantly improves albumin level plus superoxide dismutase and catalase activities of HFFD treated mice. The liver tissues of control and HFFD+AV2 treated mice showed normal hepatocytes. Conclusion: The study suggests that Aloe vera supplementation could prevent HFFD-induced oxidative stress and dyslipidemia. These findings might be used for further research on food supplementation to control metabolic disorders.